English - Spasić, Igors; Ubavić, Milan; Šumarac, Zorica; Todorović, Maša; Vučković, Biljana (Journal of Medical Biochemistry, 2020)
Abstract Aim: To investigate influence of lipid metabolism disorders on the risk of deep vein thrombosis. Methods: A total of 200 subjects participated in the study, 100 of whom experienced DVT with or without PTE, and 100 healthy subjects representing the control group. We classified patients and controls in terms of serum concentrations of chylomicrons, LDL, IDL, VLDL and HDL particles, as those with or without hyperlipoproteinemia and in terms of serum Lp(a) lipoprotein levels, as those with hyperLp(a) lipoproteinemia (serum Lp(a) values> 0.3g /l) and those without hyperLp(a) lipoproteinemia (serum Lp (a) values ​​<0.3g /l). Based on the modified and supplemented Fredrickson classification participants with verified existences of hyperlipoproteinemia were classified into subgroups based on the type of hyperlipoproteinemia. Unconditional logistic regression was used to calculate ORs with 95% CIs as a measure of the relative risks for venous thrombosis in participants with hyperlipoproteinemia compared with those without hyperlipoproteinemia. The analysis was adjusted for all potential confounders (age, sex, obesity) related to the functionality of the lipid metabolism, and at the same time may have an impact on the risk of venous thrombosis. Results: The results of the comparison of the mean values of individual lipid status parameters between the patient group and the control group clearly indicate higher concentrations of total cholesterol (5.93mmol/l vs. 5.52mmol/l), total triglycerides (1.58mmol/l vs. 1.50mmol/l), and LDL-cholesterol (3.83mmol/l vs. 3.44mmol/l) in the patient group relative to the control group, with a statistically significant difference observed only in the case of LDL-cholesterol concentrations. We have found that type IIa hyperlipoproteinemia is associated with a nearly double increased risk for deep vein thrombosis (OR 1.99; Cl 1.01-3 , 90), while type IIb, IV, or hyperLp (a) lipoproteinemia didn’t influence the risk (OR 1,22; 95% Cl 0.79-1.84; OR 0.89; 95% Cl 0.52-1.54 OR 1.85; 95% CI 0,84-4,04. Conclusion: Hypercholesterolemia doubles the risk of deep vein thrombosis development.